Promoting the Use of Carved Bamboo Utensils as Sustainable Alternative at School: An Analysis of Mechanical Strength and Thermal Resistance (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study addresses the critical environmental challenge of single-use plastic-based utensils by evaluating carved bamboo utensils made from Bambusa blumeana as a substitute. Utilizing a quantitative mixed-method framework, the research subjected both bamboo utensils (experimental group) and conventional plastic-based utensils (control group) to stress profiling, thermal thresholds up to 99.1 ℃, and a 14-day environmental exposure, as well as the use of descriptive survey of twenty-five purposively selected consumers in Maigo, Lanao del Norte. The outcomes reveal that the fibrous structure of Bambusa blumeana contains a high tensile strength of approximately 23,500 psi, compared to the structure of the plastic-based utensils. The study utilized a comparative experimental design to evaluate mechanical strength, thermal resistance, and environmental durability, complemented by a descriptive survey involving twenty-five purposively selected consumers. While the survey results indicated a high level of consumer acceptance (GWM = 4.34), the findings should be interpreted within the context of the study's limited sample size. Overall, the results suggest that integrating regional bamboo resources into institutional supply chains may be a mechanically viable and environmentally sustainable strategy for reducing dependence on single-use plastic utensils.